ANALISIS PENERAPAN ISAK NOMER 35 PADA YAYASAN JEMBER BERBAGI BERKAH BERSAMA - Wisnu, Ganes Arighi; aspirandi, rendy mirwan; Fiel Afroh, Ibna Kamelia (Balance : Jurnal Akuntansi dan Bisnis, 2023)
This study aims to find out how the presentation of financial reports at the Jember Sharing Berkah Bersama Foundation is in accordance with the concept of ISAK No. 35 and to find out the benefits of financial reports that have used ISAK No. 35 for the Jember Sharing Blessings Together Foundation. The types of data used are primary data and secondary data. Data collection techniques were carried out using interviews and documentation techniques. The data analysis method used is descriptive qualitative. The results of the research on the financial statements of the Jember Sharing Berkah Bersama Foundation are not in accordance with the perspective of ISAK No. 35, reporting is only limited to recording cash in and cash out. As with the evidence and interviews conducted by researchers with the Jember Berbagi Berkah Bersama Foundation, the Jember Berbagi Berkah Bersama Foundation has not implemented or made financial reports in accordance with this concept, so researchers implemented these financial reports